Modifying the pre-pitch entry practices of professional soccer substitutes may contribute towards improved movement-related performance indicators on match-day: A case study - Hills, S. P.; Barrett, S.; Hobbs, M.; Barwood, M. J.; Radcliffe, J. N.; Cooke, C. B.; Russell, M. (PLOS ONE, 2020)
Modifying a soccer substitute`s pre-pitch-entry activities may represent an opportunity to maximise physical performance and minimise injury-risk following match-introduction. Using a professional team that has previously participated in substitute profiling research, this follow-up case study investigated the effects of a modified match-day protocol that included substitutes; 1) performing a new pre-match warm-up alongside members of the starting team (as opposed to a separate substitute-only warm-up), 2) participating in a staff-led half-time rewarm-up (as opposed to player-led half-time activities), and 3) receiving ongoing education focusing on the efficacy of (re)warm-up activities. English Championship substitutes (n = 15) were monitored using Micro-electromechanical Systems during 13 matches incorporating the modified practices (35 observations). On an individual player basis, data were organised into bouts of warm-up activity (pre-pitch-entry) and five min epochs of match-play (post-pitch-entry). Linear mixed modelling assessed the influence of `bout` and `epoch`, position, and scoreline. Substitutes performed 3±1 rewarm-up bouts·player-1·match-1 between kick-off and pitch-entry, which were shorter (-17.2 to -27.1 min) and elicited less distance (-696 to -1257 m) than the pre-match warm-up (p=0.001). Compared with previous data, heightened absolute movement responses were observed during the pre-match and staff-led half-time (re)warm-ups, alongside greater relative distances covered during player-led activities performed between kick-off and pitch-entry. Whilst less distance (-10%) was covered during the second versus first five min period following match-introduction, values remained higher than previously reported. Between pitch-entry and the end of the match, the scoreline improved and worsened following 26% and 11% of substitutions, respectively; a favourable record compared with existing observations. Acknowledging the likely contribution from external factors, this case study reports heightened movement profiles and improved match scorelines when pre-pitch-entry practices were modified. Practitioners should note the potential influence of match-day activities on the physical responses of soccer substitutes and, if deemed necessary, consider adapting their pre-pitch-entry routines accordingly.